Determining the relationship of biochemical blood parameters with the development of cognitive impairment in working-age patients with acute myocardial infarction - Stroienko, K.; Khyzhniak, A.; Ostapets, M. (Journal of Education, Health and Sport, 2017)
Introduction. According to the World Health Organisation data provided in January 2017, cardiovascular diseases are considered to be in the list of 10 main mortality factors. Annually about 50 thousand cases of acute myocardial infarction are recorded in Ukraine. One of causes leading to unfavourable course of acute myocardial infarction are cognitive disorders which in half of cases are found of people under 60. The aim of the work is to improve laboratory diagnostics and optimize the tactics of treating cerebral insufficiency in patients with acute myocardial infarction. Materials and methods. The study included 105 patients aged from 34 to 60 years. The patients were divided into 3 groups: the first age group (34-40 years old) included 17 patients. The 2nd age group (41-50 years old) included 29 patients. The third age group - patients 50-60 years, which included 59 patients. During the study, patients on the 1st and 10th day of the disease fixed the level of CRP, blood lipid spectrum, and also assessed the state of cognitive functions using neuropsychological methods Mini Mental State Examination, clock drawing test, test “10 words memorization” A. R. Luria Each group of patients was divided into 3 subgroups and entered, respectively, 3 treatment regimens. The first treatment regimen included quercetin. The second - quercetin + 2 ethyl-6-methyl-3-hydroxypyridine succinate. The third is quercetin + morpholinium 3-methyl-1,2,4-triazolin-5 thiocetam. Results and its discussion. On the first day of the study, in terms of neuropsychological tests, it was established that cognitive disorders were observed in 100% of patients. All patients had a significant increase in CRP level relative to the normal value (up to 6 mg / l) in the age group 34–40 years - by 3.06 times; in the age group of 40-50 years - 4.4 times; in age group 3 - 5.2 times. It was found that spacecraft increased: in the age group of 34-40 years old - by 1.8 times; in the age group of 40-50 years - 2.04 times; in the age group of 50-60 years - 3.5 times. When studying the level of CRP, a decrease in this indicator was found on the tenth day of the study relative to the first day of the disease. However, when using scheme No. 1, the concentration of CRP exceeded the physiological norm in the age group of 34–40 years by 1.3 times; in the age group of 40-50 years - 1.6 times; in the age group of 50-60 years - 2.3 times. Taking into account the therapeutic scheme No. 2, the level of CRP exceeded the norm, in particular, in the age group of 34-40 years old by 1.2 times; in the age group of 40-50 years - 1.4 times; in the age group of 50-40 years old by 1.7 times. When using the treatment scheme 3, in the age group of 34-40 years, the level of CRP returned to normal, and in groups of patients of older age groups it was slightly higher than normal. Also, the data obtained indicate that there has been a tendency to a decrease in CA in patients of all age groups. For the 1st treatment regimen, the indicators of spacecraft in the first group were 1.3; in the 2nd group - 1.5; in the 3rd group - 1.7. For the 2nd treatment regimen, the indicators of CA in the first group were - 1.6, in the 2nd group - 1.3; in the 3rd group - 1.6. According to the 3rd treatment regimen, the rates of CA in the first group were 0.8, in the 2nd group - 1.4; in the 3rd group - 1.6. Conclusions: All patients had a significant increase in CRP and CA levels with respect to the normal value on the first day of the disease, but based on the results of the studies performed on the tenth day of therapy in patients of different age groups suffering from AMI and had cognitive disorders, it can be argued with a high degree of confidence that the use of therapeutic regimen 3 using 3-methyl-1,2,4-triazolin-5 thiocetam morpholinium as a potential antihypoxant resulted in a decrease in tissue hypoxia In turn, reduces the development of inflammatory reactions and CRP as one of the indicators of acute phase. When applying therapy, CA decreased in patients of all age groups. The CA index was the lowest in the age group of 34–40 years old when using the therapeutic scheme 3, which correlated with the acute phase CRP index and indicated a decrease in hypoxia, as a result of the developed inflammatory reaction and the development of local atherosclerosis.